1999
DOI: 10.1111/j.1348-0421.1999.tb01221.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Cord Factor (Trehalose 6,6′‐Dimycolate) IgG Antibody in Tuberculosis Patients Recognizes Mycolic Acid Subclasses

Abstract: The detection of anti‐cord factor (trehalose 6,6′‐dimycolate) IgG antibody in active (smear‐and/or culture‐positive) and inactive (smear‐ and culture‐negative) tuberculosis patients is a useful serodiagnostic tool that can be used for early clinical diagnosis of the disease. We estimated the titers of anticord factor IgG antibody in the sera of tuberculosis patients, and compared them with those of Mycobacterium avium‐infected patients. Most of the serum samples obtained from the tuberculosis patients were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…Later studies using a different immunization method (emulsified pure antigen rather than carrier protein-conjugated antigen) and more sensitive detection systems revealed that antisera against either M. tuberculosis or M. avium cord factor raised in rabbits preferentially recognized TOM from the species used as antigen source (21,22), suggesting that the underlying IgG antibodies were directed not against the carbohydrate backbone but against mycolic acids as the molecular components conferring species specificity. These results could subsequently be confirmed with sera of human patients infected with M. tuberculosis or M. avium: the patient sera were primarily reactive against cord factor of the infecting mycobacterial species, which independently had been determined bacteriologically (69).…”
Section: Humoral Responsesupporting
confidence: 63%
“…Later studies using a different immunization method (emulsified pure antigen rather than carrier protein-conjugated antigen) and more sensitive detection systems revealed that antisera against either M. tuberculosis or M. avium cord factor raised in rabbits preferentially recognized TOM from the species used as antigen source (21,22), suggesting that the underlying IgG antibodies were directed not against the carbohydrate backbone but against mycolic acids as the molecular components conferring species specificity. These results could subsequently be confirmed with sera of human patients infected with M. tuberculosis or M. avium: the patient sera were primarily reactive against cord factor of the infecting mycobacterial species, which independently had been determined bacteriologically (69).…”
Section: Humoral Responsesupporting
confidence: 63%
“…Recently, mycoloyl glycolipids have been reported to be a unique lipid antigen restricted by the CD-1 antigen presentation molecule (Beckman et al, 1994;Moody et al, 1997Moody et al, , 1999Niazi et al, 2001). Furthermore, it has been found that human patient sera (IgG) against TDM from either M. tuberculosis or the Mycobacterium aviumintracellulare group recognized each respective TDM from the species used as the antigen source (Enomoto et al, 1998;Pan et al, 1999), suggesting that the underlying IgG antibodies were directed not against the carbohydrate backbone, but against the mycolic acid moiety. Therefore, determination of the precise molecular structure of TDM is essential, particularly focussing on the mycolic acid moiety.…”
Section: Introductionmentioning
confidence: 99%
“…TDM exists as cell wall bound and secreted forms. TDM bound to the mycobacterial cell wall is non-toxic and protects mycobacteria from killing by the host's macrophages (Hunter et al, 2006;Pan et al, 1999). Secreted TDM accumulates with host lipids in alveoli, a process that rapidly produces caseation necrosis that leads to cavities.…”
mentioning
confidence: 99%